The Influence of TAM In E-Health Implementation: A Study of Public Health Centers in Surabaya - Nuruz Zakiyah; Bagus Nuari Hermawan (Journal of Governance and Social Policy, 2025)
Surabaya is the second largest metropolitan city in Indonesia. This has given rise to several new problems, one of which concerns health. Health services at Surabaya community health centers have experienced several problems, such as long queues and limited public access to service information. Therefore, the Surabaya City government has implemented an innovation called E-Health. The goal is to eliminate long queues at public health centers. However, in its implementation, E-Health still faces obstacles, such as a lack of public awareness of E-Health and significant disparities in the use of E-Health among public health centers. Therefore, this study aims to determine whether there is an influence between the Technology Acceptance Model (TAM) on the use of E-Health at the Sawah Pulo Community Health Center in Surabaya. The method used in this study is descriptive quantitative. The results of this study are that out of 8 hypotheses, two hypotheses are rejected: POL has no significant effect on MD and I has no significant effect on MD. Meanwhile, 6 hypotheses were accepted, namely PT had a significant effect on MD, KPT had a significant effect on KPT, KF had a significant effect on KMT, KC had a significant effect on KMT, K had a significant effect on KMT and KMT had a significant effect on MD